2022
DOI: 10.3389/fevo.2022.971429
|View full text |Cite
|
Sign up to set email alerts
|

Increased availability of preferred food and decreased foraging costs from degraded grasslands lead to rodent pests in the Qinghai-Tibet Plateau

Abstract: The increased population density of rodent species during ongoing grassland degradation further deteriorates its conditions. Understanding the effects of grassland degradation on rodent feeding habits is of great value for optimizing grassland management strategies. In this study, lightly degraded (LD), moderately degraded (MD), severely degraded (SD), and reseeded grassland (RG) were selected and their plant resources and soil physical properties were investigated. In addition, the study used ITS2 barcode com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…The severity of environmental change caused by human activities is increasing (IPCC, 2022) [ 1 ]. For example, droughts resulting from climate change can precipitate the degradation of grasslands, the reduction in vegetation diversity, and the decline in food selectivity and availability among herbivores [ 2 4 ]. Additionally, toxic weeds quickly become the dominant species in the process of grassland degradation, increasing the difficulty for herbivores to forage.…”
Section: Introductionmentioning
confidence: 99%
“…The severity of environmental change caused by human activities is increasing (IPCC, 2022) [ 1 ]. For example, droughts resulting from climate change can precipitate the degradation of grasslands, the reduction in vegetation diversity, and the decline in food selectivity and availability among herbivores [ 2 4 ]. Additionally, toxic weeds quickly become the dominant species in the process of grassland degradation, increasing the difficulty for herbivores to forage.…”
Section: Introductionmentioning
confidence: 99%
“…The first is the influence of livestock grazing on zokor density by changing soil and plant properties 16 18 . For example, Harris et al (2015) 19 found that zokor density is positively correlated with grazing intensity because the dominant plants of degraded grassland were preferred by plateau zokors, such as Potentilla anserina , Geranium wilfordii , and Taraxacum mongolicum 20 . Conversely, grazing destroys tunnels and the food resources of rodents and reduces their population in grasslands 11 .…”
Section: Introductionmentioning
confidence: 99%